Validation of the Ottawa Troponin Pathway. (March 2022) - Lam, Brandon; Li, Jesse (Junyi); Mukarram, Muhammad; Nemnom, Marie-Joe; Booth, Ronald A.; Thiruganasambandamoorthy, Venkatesh
Abstract: Background: The Ottawa Troponin Pathway (OTP) was developed to improve Non-ST elevation myocardial infarction (NSTEMI) diagnosis accuracy using 3-h serial conventional troponin I (TnI) measurements. We sought to validate the OTP in patients with TnI values >99th percentile upper reference limit (>45 ng/L). Methods: We conducted a health records review in adult patients with NSTEMI symptoms with at least two serial TnI and at least one >45 ng/L at two emergency departments (EDs). We collected baseline characteristics, ED management and disposition. 30-day outcomes included death due to cardiac ischemia, an unknown cause, or NSTEMI. Results: 635 patients were included, and 107 patients were diagnosed with NSTEMI within 30-days. 217 patients had at least one TnI value >45 ng/L but <100 ng/L, of whom 4 patients were diagnosed with NSTEMI. 418 patients had at least one TnI value ≥100 ng/L, and 103 were diagnosed with NSTEMI. The OTP accurately identified all 107 patients with NSTEMI: sensitivity and specificity was 100% (95% CI 96.6%–100%) and 32.2% (95% CI 28.2%–36.4) respectively. Conclusions: The OTP is validated among patients with TnI values above the 99th percentile with symptoms concerning for ACS. Using OTP will allow for early referral and discharge home and improve ED crowding. REB Number: 20180393-01H.